1984
DOI: 10.1111/j.1545-5300.1984.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Alliances in Nondistressed and Multiproblem Families

Abstract: The goal of this study was empirically to investigate differences between distressed and nondistressed families in the strength, patterning, and cross-situational consistency of alliances. Audiotapes were made of 12 distressed and 12 nondistressed families in two observational situations. The resultant interaction was then coded for family alliances by trained observers. Distressed families were characterized by low overall levels of alliance behavior, weakness in the marital alliance relative to other family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 25 publications
4
44
0
Order By: Relevance
“…Besides, the parent in the coalition may increasingly use psychological control mechanisms, such as guilt induction, in order to keep the child in emotional alliance (Fauber et al, 1990). And finally, the child may be placed in a loyalty conflict because of having to choose between parents (Gilbert et al, 1984). As a consequence, the child may judge the relationship with his or her parent as more negative than will the parent.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, the parent in the coalition may increasingly use psychological control mechanisms, such as guilt induction, in order to keep the child in emotional alliance (Fauber et al, 1990). And finally, the child may be placed in a loyalty conflict because of having to choose between parents (Gilbert et al, 1984). As a consequence, the child may judge the relationship with his or her parent as more negative than will the parent.…”
Section: Discussionmentioning
confidence: 98%
“…Findings from studies of cross-generational coalitions suggest that although there are differences in patterns of family relations between families of referred and nonreferred children, the former are not by definition characterised by cross-generational coalitions (Gilbert, Christensen, & Margolin, 1984 ;Madanes, Dukes, & Harbin, 1980 ;Mann, Borduin, Henggeler, & Blaske, 1990). An important limitation of research in this field is that the question whether children who are involved in a cross-generational coalition had more problem behaviour 479 MUTUAL FAMILY RELATIONS AND CHILD PSYCHOPATHOLOGY than children from families without such cross-generational coalitions is not addressed.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, other couples may experience increases and decreases in marital quality as they become more or less successful at maintaining an alliance or may experience more or less incongruence as the quality of the marriage fluctuates. The idea that transitions are handled differently in different families is reflected in early theorizing about the flexibility of alliances in dysfunctional versus functional families (see Gilbert et al, 1984). More intensive diary data or qualitative data may help to illuminate these processes.…”
Section: Discussionmentioning
confidence: 99%
“…First, research from the field of family therapy suggests that, when subsystem boundaries are not maintained, parent‐offspring coalitions and marital dysfunction ensue (Minuchin, 1985). Both weak marital alliances and discrepant parent‐child alliances characterize distressed families (Gilbert, Christensen, & Margolin, 1984; Minuchin, 1974). Researchers have theorized that mothers in dissatisfying marriages compensate by becoming overinvolved with one child or displace their tension by exhibiting more conflict with one child (Gilbert et al).…”
Section: Incongruence In Parental Differential Treatment: a Family‐lementioning
confidence: 99%
“…Furthermore, discrepant levels of parental involvement in triadic play predict later teacher rated anxiety, and interparental hostility and competitiveness in such interactions predict more aggression (McHale & Rasmussen, 1998). Based on research (Gilbert, Christensen, & Margolin, 1984) and theory, one would expect that unbalanced triadic interactions may be especially common for distressed couples: Men experiencing marital distress often withdraw from family life (Amato, 1986;Belsky, Rovine, & Fish, 1989;Christensen & Heavey, 1990;Gottman & Levenson, 1988), whereas some have argued that mothers may compensate for marital distress by becoming increasingly involved with children (Brody, Pellegrini, & Sigel, 1986; see also Biller, 1995;Dunn, 1988; but see Erel & Burman, 1995). However, McHale (1995) found that parenting discrepancy (triadic balance) was not significantly associated with husband or wife reports of marital quality.…”
Section: Joint Family Managementmentioning
confidence: 99%